Single cell transcriptomics correlate avian coronavirus prime vaccination efficacy with antigen-presenting cell preference - Xuefeng Li; Yumeng Liang; Yu Zhang; Botao Fa; Zheyi Liu; Lu Cui; Miaomiao Xi; Shufeng Feng; Li Xu; Xiaoxiao Liu; Zhengtao Xiao; Shengwang Liu; et al. (npj Vaccines)
Abstract Biosafe and effective vaccines are urgently needed for the prevention and control of avian infectious bronchitis virus (IBV), the first coronavirus to be discovered, despite extensive vaccination for decades. However, their development has been hindered by our limited understanding of prime vaccination, which is crucial for rational vaccine design. Here, we constructed in vivo dynamic single-cell resolution blood immune landscapes of chickens immunized with live-attenuated or inactivated IBV. Bioinformatic analysis together with in vivo examination revealed that live-attenuated and inactivated vaccines reshaped lymphocytes and led to identical compositions through different mechanisms. Inactivated vaccines activate T lymphocytes through dendritic cells with subsequent T lymphocyte-dependent B lymphocyte expansion upon prime vaccination but induce pathogen-specific antibodies only after boost vaccination. Prime vaccination with a live-attenuated vaccine led to an initial preference for monocytes/macrophages as antigen-presenting cells (APCs), followed by extensive activation of the main APCs, which facilitated rapid T lymphocyte expansion and elicited satisfactory humoral immunity. Along with the disparate utilization of APCs, live-attenuated and inactivated vaccines yielded distinct TCR repertoires and triggered different B lymphocyte dynamics despite their similar final BCR repertoires. Furthermore, APC preference correlated with vaccine effectiveness rather than modality, as prime avian influenza vaccination triggered effective adaptive immune responses with the same APC preference as live-attenuated IBV did. This study comprehensively characterized avian coronavirus prime vaccination and highlighted the key role of APC preference.